2011
DOI: 10.1177/1352458511428462
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of autologous T-cell therapy in multiple sclerosis: subset analysis and implications for trial design

Abstract: Background: Tovaxin is an autologous T-cell immunotherapy under investigation for the treatment of MS. The product consists of in vitro expanded myelin-reactive T-cells manufactured against up to six immunodominant peptides derived from three myelin antigens. Methods: A Phase 2b placebo controlled study (TERMS) was conducted in 150 subjects to gather safety and efficacy data in relapsing-remitting MS and clinically isolated syndrome subjects. Results: Tovaxin had a favorable safety profile. Although no statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…From available data (Fox et al 2012;Huang et al 2014), it appears that myelin basic protein (MBP), proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG) and possibly other yet-unidentified molecules can be implicated in MS development. Hence, antigenic specificity of monoclonal or oligoclonal vaccinal T-cells may be distinguished from self-reactive -cells dominating in autoimmune process by antigenic specificity of their TCR.…”
Section: Concept Of T-cell Vaccination Is Based On Multiple Immunizatmentioning
confidence: 99%
See 1 more Smart Citation
“…From available data (Fox et al 2012;Huang et al 2014), it appears that myelin basic protein (MBP), proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG) and possibly other yet-unidentified molecules can be implicated in MS development. Hence, antigenic specificity of monoclonal or oligoclonal vaccinal T-cells may be distinguished from self-reactive -cells dominating in autoimmune process by antigenic specificity of their TCR.…”
Section: Concept Of T-cell Vaccination Is Based On Multiple Immunizatmentioning
confidence: 99%
“…It has been previously shown that T-cell vaccination can be effectively used in the treatment of relapsing forms of MS (Fox et al 2012;Huang et al 2014). A progressive MS is usually less sensitive to therapeutic manipulations compared to relapsing MS.…”
Section: Concept Of T-cell Vaccination Is Based On Multiple Immunizatmentioning
confidence: 99%
“…TCV include an attenuation step to preventing the encephalitogenicity of myelin-reactive T cells and is safe. Two phase II, placebo-controlled clinical trials of TCV in MS were reported [167,168]. Fox et al showed that treatment with myelin-reactive T-cells against up to six peptides of MBP, MOG and PLP was safe in 100 RRMS and CIS patients, of which 44% were previously treated with DMTs [168].…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%
“…Two phase II, placebo-controlled clinical trials of TCV in MS were reported [167,168]. Fox et al showed that treatment with myelin-reactive T-cells against up to six peptides of MBP, MOG and PLP was safe in 100 RRMS and CIS patients, of which 44% were previously treated with DMTs [168]. Although no statistically significant clinical or radiological benefits were obtained when compared with the placebo arm, some post-hoc evidence of clinical efficacy in the active arm in the subgroup of patients DTM-naïve was seen [168].…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%
“…A randomized, placebo-controlled, phase IIb trial was conducted using myelin-specific T cells restimulated with 6 myelin peptides from MBP, MOG, and PLP proteins [Tcelna and Imilecleucel-T (Opexa Therapeutics, The Woodlands, TX, USA)] in 150 patients with RRMS [133]. After 1 year, analysis revealed no difference in clinical and radiological parameters.…”
Section: Autologous T-cell Therapymentioning
confidence: 99%